ASUHAN KEBIDANAN IBU HAMIL DENGAN PREEKLAMPSIA BERAT TRIMESTER III PADA NY. N DI PUSKESMAS KRAMATWATU TAHUN 2019 - Vega Muhida (Poltekkes 'Aisyiyah Banten, 2020)
Severe preeclampsia is a pregnancy complication characterized by the onset of hypertension 160/110 mmHg or more accompanied by proteinuria and / or with edema in pregnancies of 20 weeks or more. The incidence of severe preeclampsia at the Kramatwatu Health Center in 2018 was 26 (0.98%) of 2033 pregnant women. The purpose of this study is to be able to provide midwifery care for pregnant women with severe preeclampsia in accordance with midwifery service standards. This case study research is a qualitative case study, because it was conducted by interview using the format of assessment of pregnant women, anamnesa, physical examination, laboratory examinations, and the MCH handbook. After the assessment, it was found that Ny. N has severe preeclampsia. Therefore the researchers gave measures in the form of oxygen 5 L / min, RL infusion of 20 tpm, Dc installation, giving dexamethasone therapy 3 ampoules at a dose of 2.5 ml / ampoule, nifedipine 10 mg, furosemide 2 ampoules at a dose of 10 mg / ampoule , monitoring the general condition of the mother, referring the mother to the RSD maternal emergency room with officers. It is hoped that this case study can improve the quality of midwifery care services optimally through immediate treatment, especially for pregnant women with severe preeclampsia